The Church History Society of Southern Africa (CHSSA) attempting to come of age: the story of the CHSSA between 1991 and 2005 - J. W. Hofmeyr (Acta Theologica)
In this article, the focus is on the question whether the Church History Society of Southern Africa (CHSSA) has matured after its 35 years of existence (1970-2005) to a fairly mature theological society in the South African academic context. After an introduction, attention is given to the proposals of an ad hoc committee that investigated the reorganization of the society into a more inclusive and representative organization, the different conferences, the journal, membership and management of the society, theological traditions and positions present in the society and some perspectives on the road ahead. Without trying to provide an official audit of the society, it is finally concluded that it is attempting to come of age and the prospects for the future are relatively positive. However, only the years to come will prove whether this society has fully come of age.